Perancangan Sistem E-Commerce dan Software Point of Sale (POS) pada Restoran dan Kafe Berbasis Client Server - Martono Martono (Lembaga Pengembangan Kinerja Dosen, 2025)
E-commerce and Point of Sale (POS) software are two rapidly evolving technologies in the modern industry, particularly in the food and restaurant business. Along with this development, the need to create more efficient and user-friendly solutions is increasingly pressing. Previously developed systems, which integrate e-commerce and POS, help customers purchase food without having to go directly to the restaurant. However, these systems still have several shortcomings that can be addressed to improve the user experience, especially for consumers who desire more efficient and practical transactions. In this study, the authors focused on further developing the existing system by adding new features to enhance user convenience and satisfaction. One key development is a digital balance storage feature that simplifies transactions, allowing consumers to use their available balance to purchase food. Furthermore, the system will be equipped with a QR code that functions as a customer ID, replacing the more conventional membership card, and will be more efficient in terms of cost and access time. Other improvements include the addition of a points feature, more flexible software authority, strengthened security systems, and improvements in transaction management and reporting. This study used field observation methods, including direct observation and user interviews to gain deeper insights. Utilizing this updated system is expected to increase food sales, improve transaction processes, and provide convenience for customers who want to enjoy restaurant services without any hassles. With the development of an integrated e-commerce and POS system, customers will have a more flexible and convenient purchasing experience.